2003
DOI: 10.1128/aem.69.6.3421-3426.2003
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Engineering of Escherichia coli for Production of Enantiomerically Pure ( R )-(−)-Hydroxycarboxylic Acids

Abstract: A heterologous metabolism of polyhydroxyalkanoate (PHA) biosynthesis and degradation was established in Escherichia coli by introducing the Ralstonia eutropha PHA biosynthesis operon along with the R. eutropha intracellular PHA depolymerase gene. By with this metabolically engineered E. coli, enantiomerically pure (R)-3-hydroxybutyric acid (R3HB) could be efficiently produced from glucose. By employing a two-plasmid system, developed as the PHA biosynthesis operon on a medium-copy-number plasmid and the PHA de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
57
1
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(60 citation statements)
references
References 32 publications
0
57
1
2
Order By: Relevance
“…coli, Lee et al reported the production of 9.6 g L -1 3HB (Lee and Lee 2003). This is of great interest, but also requires careful confirmation, because there is a counter-claim that the high (R)-3HB production was not reproducible, based on both theoretical grounds and experimental evidence (Uchino et al 2008).…”
Section: Discussionmentioning
confidence: 98%
“…coli, Lee et al reported the production of 9.6 g L -1 3HB (Lee and Lee 2003). This is of great interest, but also requires careful confirmation, because there is a counter-claim that the high (R)-3HB production was not reproducible, based on both theoretical grounds and experimental evidence (Uchino et al 2008).…”
Section: Discussionmentioning
confidence: 98%
“…The quantification of 3HB by NAD-dependent 3HB dehydrogenase is possible but is also time-consuming, allows the detection of monomers only, and gives no online information for the hydrolysis reaction. 3HB oligomers that are major products of most PHB depolymerases can only be indirectly taken into account either by chemical cleavage of 3HB oligomers to monomers by alkali treatment (29) or by enzymatic hydrolysis by 3HB oligomer hydrolase (40). Some exotic methods for recording the degradation of polyesters include electron microscopy (35,38), 1 H-nuclear magnetic resonance (47), or tracking of radiolabeled polymers (18,50), but apparently, they are not suitable for routine assays.…”
Section: Discussionmentioning
confidence: 99%
“…The biosynthesis of 3HB has typically been achieved by two different mechanisms: depolymerization (in vitro or in vivo) of microbially synthesized poly-(R)-3-hydroxybutyric acid (PHB) (8,13) or direct synthesis of 3HB without a PHB intermediate (9,12,15). However, due to the stereospecific constraints of PHB synthesis, in which polymers are composed exclusively of (R)-3HB monomer units, the synthesis of (S)-3HB from PHB is effectively impossible.…”
mentioning
confidence: 99%